2021
DOI: 10.1007/s10006-021-00954-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periapical surgery on oral health-related quality of life in the first postoperative week using the Dutch version of Oral Health Impact Profile-14

Abstract: Objective To evaluate whether periapical surgery affects oral health-related quality of life (OHRQoL) within the first postoperative week. Study design The primary outcomes in 133 patients (54 men, 79 women; mean age 50.8 years) undergoing periapical surgery were the Oral Health Impact Profile-14 (OHIP-14) score and postoperative sequelae, including pain, analgesic intake, swelling, limited mouth opening, chewing difficulties, and postoperative infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“… 37 , 39 , 44 , 68 , 69 Studies have reported OHRQoL improvement after primary 37 , 40 , 57 , 66 and secondary 67 nonsurgical root canal treatment as well as surgical endodontic treatment. 52 Conversely, studies have also reported no significant difference in OHRQoL after nonsurgical treatment. 60 , 63 These contrasting findings may be explained by the heterogeneity of endodontic patients in the disease- (ie, preoperative symptoms), treatment- (ie, complications), and patient-related factors (ie, experience of the treatment, psychosocial factors, and patient values).…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“… 37 , 39 , 44 , 68 , 69 Studies have reported OHRQoL improvement after primary 37 , 40 , 57 , 66 and secondary 67 nonsurgical root canal treatment as well as surgical endodontic treatment. 52 Conversely, studies have also reported no significant difference in OHRQoL after nonsurgical treatment. 60 , 63 These contrasting findings may be explained by the heterogeneity of endodontic patients in the disease- (ie, preoperative symptoms), treatment- (ie, complications), and patient-related factors (ie, experience of the treatment, psychosocial factors, and patient values).…”
Section: Reviewmentioning
confidence: 99%
“…There was no correlation between OHIP-14 sores and healing outcome. Tuk et al 2021 52 Prospective study; Amsterdam 133 patients Surgical endodontic treatment Every day from the day of surgery to 7 days postoperatively OHIP-14 Dutch version supplemented with questions on postoperative symptoms No OHRQoL generally improved throughout the week (OHIP-14 score decreased). There were significant differences in OHRQoL associated with various factors (age, postoperative infection, smoker).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations